ANALISIS DAMPAK PANDEMI COVID 19 TERHADAP RESIKO PENINGKATAN KEMISKINAN DI INDONESIA - Wibisono, Randika (Salam (Islamic Economics Journal), 2022)
Poverty is an index that can see how a country is successful in development. In Indonesia, the poverty rate is high along with the increasing impact of the Covid-19 pandemic from time to time. Poverty is a complex problem. From the past until now this problem is still there, even increasing. Poverty is still a persistent problem facing Indonesia. This proves that poverty is not a trivial problem. Serious efforts are needed from various components of society and the government to work together in tackling poverty.This study aims to analyze poverty caused by the Covid-19 pandemic. From an economic perspective, the Covid-19 pandemic has brought some economic sector activities to a standstill. The impact of the Covid-19 pandemic on the economy is of particular concern in this study. In the financial sector, directly, the Covid-19 pandemic has had a significant impact on increasing the number of poverty.The method used in this research is literature review. The results of the study show that the Indonesian government has made poverty alleviation efforts for a long time by making policies that are considered capable of overcoming the problem of poverty. These policies include Direct Cash Assistance (BLT), Family Hope Program (PKH), Smart Indonesia Program (PIP), and other programs. These programs aim to increase the lower class to overcome poverty Keywords: poverty, economic, policy